Politics of Islamic Law in Indonesia: Indonesianization of Islamic Law - Kamsi Kamsi (Faculty of Sharia and Law - Sunan Kalijaga State Islamic University, 2018)
Abstract: Indonesianization of Islamic law contains two tendencies; first, is the ideal of building Islamic law that characterizes Indonesia by freeing itself from Arab culture and making Indonesian custom as one of the sources of Islamic law. The peak is marked by the emergence of the concept of Jurisprudence of Indonesia. The second tendency is constitutional-oriented Indonesianness, which is to formulate Islamic law in the form of legislation through consensus (Ijma`) of Indonesian clerics. The author argues that such a process of Islamic law becomes a national law. Given Indonesia is a country with a population of bhinneka (Plurality). In this article the author analyzes with the theory of differentiation in unification that is paying attention to diversity (plurality), in the form of a codification of law that contains legal unification as well as legal differentiation. And in the process of enactment toward the Indonesianization of the law it is necessary to note the existence of the national guidance principles, namely: the law in Indonesia must guarantee the integration or the integrity of the nation, the law must be created democratically, the law must encourage the creation of social justice and must pay attention to the principles of humanity, principles of human rights, and the principle of equality before the law.Abstrak: Indonesianisasi hukum Islam mengandung dua kecenderungan; pertama, adalah cita-cita membangun hukum Islam yang berciri khas Indonesia dengan membebaskan diri dari budaya Arab dan menjadikan adat Indonesia sebagai salah satu sumber hukum Islam. Puncaknya ditandai dengan munculnya konsep fikih Indonesia. Kecenderungan kedua adalah keindonesiaan yang berorientasi konstitusional, yakni memformulasikan hukum Islam dalam bentuk peraturan perundang-undangan melalui konsensus (Ijma`) ulama Indonesia. Penulis berpendapat bahwa proses demikian menjadikan hukum Islam sebagai hukum nasional. Mengingat Indonesia adalah negara dengan penduduk yang plural. Dalam artikel ini penulis menganalisis dengan teori diferensiasi dalam unifikasi yaitu memperhatikan pluralitas, dalam bentuk satu kodifikasi hukum yang mengandung unifikasi hukum sekaligus diferensiasi hukum. Dalam proses pemberlakuan menuju Indonesianisasi hukum perlu diperhatikan adanya kaedah-kaedah penuntun nasional, yaitu: hukum di Indonesia harus menjamin integrasi bangsa, hukum harus diciptakan secara demokratis, hukum harus mendorong terciptanya keadilan sosial, dan harus memperhatikan prinsip kemanusiaan, prinsip hak asasi manusia, dan prinsip persamaan di depan hukum.